Healthcare provider-focused antimicrobial stewardship in sub-Saharan Africa: opportunities and challenges - Dunlea, T.; Richards, Shauna; Lembo, T. (Elsevier, 2023)
To address the antimicrobial resistance (AMR) crisis, governments around the world have created action plans to optimize antimicrobial use (AMU). These plans include antimicrobial stewardship (AMS) that encompasses educational programs for healthcare workers. We discuss these programs in sub-Saharan Africa, including the opportunities and challenges arising from a highly constrained healthcare environment.